2013
DOI: 10.1007/s00330-013-2966-z
|View full text |Cite
|
Sign up to set email alerts
|

Imaging features of sporadic breast cancer in women under 40 years old: 97 cases

Abstract: The imaging characteristics of cancers in patients under 40 years without proven gene mutations do not differ from their older counterparts, but appear correlated to phenotypic profiles, which have a different distribution in young women compared to the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
25
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 30 publications
22
25
3
1
Order By: Relevance
“…In many countries, asymptomatic women under 40 years of age are usually not recommended for mammographic breast cancer screening due to the possible hazards of regular exposure to radiation and cost-benefit issues related to having dense breast tissue (18). Furthermore, the Ko- (8) 11 (14) 1 (3) showed calcifications when including the mass with calcification, and this was consistent with a previous report (20).…”
Section: Discussionsupporting
confidence: 80%
“…In many countries, asymptomatic women under 40 years of age are usually not recommended for mammographic breast cancer screening due to the possible hazards of regular exposure to radiation and cost-benefit issues related to having dense breast tissue (18). Furthermore, the Ko- (8) 11 (14) 1 (3) showed calcifications when including the mass with calcification, and this was consistent with a previous report (20).…”
Section: Discussionsupporting
confidence: 80%
“…In our study, the positive predictive value of mammography for diagnosis was 80.5%, which is within the previously reported range (50-90%) [17,18]. The reason for all the false-negative cases was that extremely dense parenchyma obscured the lesion (breast tissue composition, d).…”
Section: Discussionsupporting
confidence: 75%
“…The revised BI-RADS provides uniform terminology in the lexicon across all three imaging modalities: mammography, ultrasound (US), and magnetic resonance imaging (MRI) [16]. There have been several reports on the radiological features of breast cancer in young women with different age cut-offs [17][18][19], but most studies did not use the revised BI-RADS.…”
Section: Introductionmentioning
confidence: 99%
“…Despite there was no statistically significant difference in the imaging findings of molecular subtypes, we observed that the presence of calcifications at mammography was more common in HER2 subtype and oval/round mass at ultrasound was more common in triple-negative subtype, which was also described in previous studies [18,19].…”
Section: Discussionsupporting
confidence: 72%